The technology acceptance model and SMS usage in Singapore. - Song, Yeow Chung. (2008)
This study seeks to examine the various factors affecting post adopters’ usage decisions of SMS applications. We postulate that independent constructs affect post adopters’ usage decisions mainly through intention to continue usage, which would consequently affect extent of usage (actual usage). By integrating multi-disciplinary theories such as Technology Acceptance Model, Rogers’ Innovation Diffusion Theory and Social Identity Theory, we propose and empirically validate a research model.